Life Cycle Assessment of Anaerobic Digestion Pathways for Winery Residues: Influence of Functional Unit Selection on Wastewater Treatment and Grape Pomace Valorization - Mara Silva; Vitor Coelho Barroso; José Pereira; Ana Catarina Faria (Recycling, 2026)
Winery activities generate large amounts of residues requiring sustainable management. Anaerobic digestion offers opportunities for resource recovery while reducing the environmental burdens associated with these residues. This study presents a gate-to-gate Life Cycle Assessment (LCA) of two anaerobic digestion pathways: winery wastewater treatment (Scenario A) and grape pomace valorization (Scenario B). Inventory data were obtained from pilot-scale operation and complemented with the Ecoinvent 3.10 database. Environmental impacts were assessed using the ReCiPe 2016 Midpoint (H) method across seven impact categories. To ensure comparability, results were evaluated using both process-based functional units and an energy-normalized functional unit of 1 MJ of useful electricity, applied as an exploratory indicator of energy-recovery intensity under pilot-scale conditions. Although grape pomace digestion showed higher impacts per unit of substrate processed, it achieved lower impacts per MJ of electricity generated, with reductions of approximately 8–10 times across categories. Higher methane yields and lower electricity demand were contributors to this performance. However, both pilot-scale systems exhibited negative net electricity balances, indicating that the energy-normalized comparison represents energy-recovery intensity rather than net energy delivery. The findings highlight the importance of functional unit selection and the complementary role of both pathways in circular winery residue management.